2023
DOI: 10.1021/acsanm.2c05433
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Copper(II) Oxide Nanostructures with Different Morphologies for Nonenzymatic Glucose Sensing

Abstract: The glucose sensitivity achieved with copper(II) oxide particles with three different morphologies (spheres, platelets, and needles) for application in nonenzymatic glucose sensors was investigated. The morphologies of CuO nanoparticles were controlled by different synthesis parameters, including changes in precipitators of Cu(II) ions, pH values, calcination protocol, and the addition of surfactant and hydrogen peroxide. The role of copper(II) oxide particle morphology in nonenzymatic glucose sensing was stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…TENGs are a cutting−edge technology that converts mechanical energy into electrical energy by exploiting the combined effects of the triboelectric effect and electrostatic induction. When two dissimilar materials with different electron affinities come into contact, they exchange electrons, creating opposite charges on their surfaces [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. The repeated contact–separation or relative sliding motion of the materials generates an alternating current (AC) output.…”
Section: Operating Principlementioning
confidence: 99%
“…TENGs are a cutting−edge technology that converts mechanical energy into electrical energy by exploiting the combined effects of the triboelectric effect and electrostatic induction. When two dissimilar materials with different electron affinities come into contact, they exchange electrons, creating opposite charges on their surfaces [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. The repeated contact–separation or relative sliding motion of the materials generates an alternating current (AC) output.…”
Section: Operating Principlementioning
confidence: 99%
“…By ingeniously harnessing energy from ever-present ambient sources, such as the natural kinetic motion of blood flow or subtle temperature gradients within the body, P-TENGs offer a remarkable solution to the challenges of powering electronic devices for biomedical applications [92][93][94][95][96][97][98][99]. By circumventing the need for cumbersome external power supplies or the inconvenience of recurrent battery replacements, P-TENGs pave the way for seamless and sustainable biomolecular sensing.…”
Section: Glucose and Proteinmentioning
confidence: 99%
“…Copper (Cu) nanomaterials, including nanoparticles and nanowires, have garnered significant attention in the development of nonenzymatic glucose sensors due to their notable attributes, such as high electrocatalytic activity, cost-effectiveness, and stability. It has been revealed that precise control over the nanostructure plays a crucial role in achieving efficient electrocatalytic performance for glucose-sensing applications. , In this regard, nanoporous copper thin films (CuTFs) have emerged as a promising candidate, offering improved electrocatalytic activity owing to their enlarged surface area, enhanced charge and mass transfer, and compatibility with external electrical connections . However, limited reports can be found regarding the application of nanoporous CuTFs in nonenzymatic glucose sensors, highlighting a research gap in the field.…”
Section: Introductionmentioning
confidence: 99%